Providing a Framework for Performance Evaluation of Organizations in Successfully Implementing TQM, Based on Knowledge Management Approach and Organizational Agility - Neda Irannejad; Hadi Shirouyehzad; Arash Shahin (Complexity)
Nowadays, any organization, in order to be aware of the desirability and quality of its activities, especially in dynamic environments, urgently needs an evaluation system to assess its system’s performance and efficiency. In this study, the performance of production and service organizations has been evaluated according to the effect of knowledge management success factors and organizational agility on the success factors of total quality management (TQM (total quality management)). Considering that the two areas of knowledge management and organizational agility are among those influential on TQM and each has been examined separately in the previous studies in relation to it, none of the previous studies has focused on all these three areas together. Therefore, in the present study, in addition to evaluating the performance of organizations based on the success factors of TQM, we seek to identify the influential factors and success factors of each of the three areas of knowledge management, organizational agility, and TQM; then, the impact of knowledge management and organizational agility on the success factors of TQM is evaluated. To express the above-given relationship, group interpretive structural modelling (ISM (interpretive structural modelling)) techniques have been used to rank the components of each domain; also, fuzzy quality function deployment (FQFD (fuzzy quality function deployment)) technique has been applied to find the weight and relationship of the three mentioned domains by examining the independent and interface variables of the previous step. The weights resulting from two-stage house of quality have been used as the weights for the design of the two-stage data envelope analysis (DEA) model by the weight control method. Finally, the above-given factors in knowledge-based companies located in Khorramabad Science and Technology Park have been studied and the results have been expressed.